Implementasi Kebijakan Perlindungan Lahan Pertanian Pangan Berkelanjutan Di Kecamatan Pakusari Kabupaten Jember - Wijaksono, Agung; Maulana , Akbar (Jurnal Agregasi, 2025)
Agricultural land is the center of income and food production for the community. This will have a huge impact if agricultural land shrinks every year. This research aims to examine the implementation of sustainable food agricultural land protection policy in Jember Regency, with a special focus on Pakusari Sub-district. Using a descriptive qualitative approach with a case study method, this research collected primary data through in-depth interviews and field observations. Secondary data was obtained through analyzing policy documents, official reports, and statistical data. The results show that policy implementation in Pakusari Sub-district faces several challenges, including a lack of policy socialization to farmers, limited resources, and conflicts of interest between agricultural businesses and land developers. Nonetheless, the local government is working to increase awareness and compliance with this policy. Key findings from this research include stakeholder engagement, Socialization and Education and Monitoring and Evaluation. Conclusion this research emphasizes the importance of better coordination between the local government, farmer groups and communities in implementing the sustainable food agricultural land protection policy in Jember District.